The fiscal anatomy of a regulatory polity: Tax policy and multilevel governance in the EU - Philipp Genschel; Markus Jachtenfuchs (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2010)
The paper analyzes the common assumption that the EU has little power over taxation. We find that the EU's own taxing power is indeed narrowly circumscribed: its revenues have evolved from rather supranational beginnings in the 1950s towards an increasingly intergovernmental system. Based on a comprehensive analysis of EU tax legislation and ECJ tax jurisprudence from 1958 to 2007, we show that at the same time, the EU exerts considerable regulatory control over the member states' taxing power and imposes tighter constraints on member state taxes than the US federal government imposes on state taxation. These findings contradict the standard account of the EU as a regulatory polity which specializes in apolitical issues of market creation and leaves political issues to the member states: despite strong safeguards, the EU massively regulates the highly salient issue of member state taxation.
Keywords: 330; Steuerpolitik; EU-Steuerrecht; Rechtsprechung; Governance-Ansatz; EU-Staaten